Barriers to healthcare coordination in market-based and decentralized public health systems: A qualitative study in healthcare networks of Colombia and Brazil (2016)
Although integrated healthcare networks (IHNs) are promoted in Latin America in response to health system fragmentation, few analyses on the coordination of care across levels in these networks have been conducted in the region. The aim is to analyse the existence of healthcare coordination across levels of care and the factors influencing it from the health personnel' perspective in healthcare networks of two countries with different health systems: Colombia, with a social security system based on managed competition and Brazil, with a decentralized national health system. A qualitative, exploratory and descriptive-interpretative study was conducted, based on a case study of healthcare networks in four municipalities. Individual semi-structured interviews were conducted with a three stage theoretical sample of (a) health (112) and administrative (66) professionals of different care levels, and (b) managers of providers (42) and insurers (14). A thematic content analysis was conducted, segmented by cases, informant groups and themes. The results reveal poor clinical information transfer between healthcare levels in all networks analysed, with added deficiencies in Brazil in the coordination of access and clinical management. The obstacles to care coordination are related to the organization of both the health system and the healthcare networks. In the health system, there is the existence of economic incentives to compete (exacerbated in Brazil by partisan political interests), the fragmentation and instability of networks in Colombia and weak planning and evaluation in Brazil. In the healthcare networks, there are inadequate working conditions (temporary and/or part-time contracts) which hinder the use of coordination mechanisms, and inadequate professional training for implementing a healthcare model in which primary care should act as coordinator in patient care. Reforms are needed in these health systems and networks in order to modify incentives, strengthen the state planning and supervision functions and improve professional working conditions and skills. © 2015 The Author 2016. Published by Oxford University Press in association with The London School of Hygiene and Tropical Medicine.